1990
DOI: 10.1159/000146981
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepithelial Endocrine Cells in the Lung of the Lungfish Protopterus aethiopicus

Abstract: The occurrence and distribution of neuroepithelial endocrine (NEE) cells was demonstrated electron- and fluorescence-microscopically in the lungfish Protopterus aethiopicus. They were only found to occur solitarily in the basal part of the ciliomucous epithelium which is restricted to the pneumatic duct and adjacent parts of the common anterior chamber. The NEE cells show a yellow, formaldehyde-induced fluorescence. Electron-microscopically, all the NEE cells are characterized by membrane-bound electron-dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…The occurrence in the apical cytoplasm of rough endoplasmic reticulum, a Golgi complex, electronlucent vesicles located in close proximity to the Golgi apparatus and just beneath the luminal plasma membrane, as well as coated vesicles are morphological features that are suggestive of a secretory activity on the apical pole of some NEE cells (Haller, 1993). Similar apical vesicles indicating a process of exocytosis were reported in NEE cells of a lungfish (Adriaensen et al, 1990). However, the content of the apical secretory vesicles is as yet undetermined.…”
Section: General Reflectionssupporting
confidence: 77%
“…The occurrence in the apical cytoplasm of rough endoplasmic reticulum, a Golgi complex, electronlucent vesicles located in close proximity to the Golgi apparatus and just beneath the luminal plasma membrane, as well as coated vesicles are morphological features that are suggestive of a secretory activity on the apical pole of some NEE cells (Haller, 1993). Similar apical vesicles indicating a process of exocytosis were reported in NEE cells of a lungfish (Adriaensen et al, 1990). However, the content of the apical secretory vesicles is as yet undetermined.…”
Section: General Reflectionssupporting
confidence: 77%
“…Similar apical vesicles indicating a process of exocytosis were reported in NEE cells of a lungfish (Adriaensen et al, 1990). However, the content of the apical secretory vesicles is as yet undetermined.…”
Section: General Reflectionssupporting
confidence: 77%
“…The base of the cell contains numerous dense-cored vesicles, 80-165 nm in diameter, and is adjacent to the basement membrane, but appears to lack innervation. The fine structure in Protopterus was described by Adriaensen et al (1990), who demonstrated the presence of neuro-endocrine cells in the pneumatic duct region. The cytology was similar but the dense-cored vesicles somewhat smaller than in Polypterus (30-150 nm) and the neuro-endocrine cells were innervated.…”
Section: Paraneurons In the Lungs Of Air-breathing Fishesmentioning
confidence: 97%